American GI Forum 1993 - San Jose Queen Coronation (and Other Event) - Castellano, Alcario:::creator:::::::::::: (2024)
Video and transcripts of the 1993 American GI Forum - San Jose chapter Queen Coronation. Also included is a video of the 1993 Fiestas Patrias Parade celebrating Mexico's Day of Independence (1:19:57).